Simultaneous Vehicle and Crew Routing and Scheduling for Partial- and Full-Load Long-Distance Road Transport - Michael Drexl; Julia Rieck; Thomas Sigl; Bettina Press (BuR - Business Research, 2013)
This paper studies a simultaneous vehicle and crew routing and scheduling problem arising in long-distance road transport in Europe: Pickup-and-delivery requests have to be fulfilled over a multi-period planning horizon by a heterogeneous fleet of trucks and drivers. Typically, in the vehicle routing literature, a fixed assignment of a driver to a truck is assumed. In our approach, we abandon this assumption and allow truck/driver changes at geographically dispersed relay stations. This offers greater planning flexibility and allows a better utilization of trucks, but also creates intricate interdependencies between trucks and drivers and requires the synchronization of their routes. A solution heuristic based on a two-stage decomposition of the problem is developed, taking into account European Union social legislation for drivers, and computational experiments using real-world data provided by a major German forwarder are presented and analyzed. The obtained results suggest that for the vehicle and driver cost structure prevalent in Western Europe and for transport requests that are not systematically acquired to complement one another, no cost savings are possible through simultaneous vehicle and crew routing and scheduling, although no formal proof of this fact is possible.
urn:nbn:de:0009-20-38122
Keywords: 650; crew scheduling; full truckload transportation; synchronization; vehicle routing